Mapping genomic regions and genes associated with the fat-tail, an adaptation trait in indigenous sheep - Mwacharo, Joram M.; Hanotte, Olivier H. (CGIAR System Organization, 2019)
Poster prepared for a share fair, Addis Ababa, May 2019